ASSOCIATION BETWEEN CANCER TYPE AND GLIM-DEFINED MALNUTRITION IN PATIENTS UNDERGOING CHEMOTHERAPY: A CROSS-SECTIONAL STUDY: HUBUNGAN ANTARA JENIS KANKER DENGAN DERAJAT MALNUTRISI BERDASARKAN KRITERIA GLIM PADA PASIEN KEMOTERAPI: STUDI POTONG LINTANG - Ridha Aryani; Dina Keumala Sari; Dedy Hermansyah; Fitriyani Nasution; Cut Adeya Adella (Faculty of Medicine Universitas Islam Sumatera Utara, 2026)
Malnutrition is a common complication in patients with cancer and is associated with poorer clinical outcomes.1 The Global Leadership Initiative on Malnutrition (GLIM) criteria provide an international consensus for diagnosing malnutrition.2 However, evidence regarding variations in malnutrition severity across different cancer types remains limited. Objective: This study aimed to evaluate the association between cancer type and malnutrition severity defined by the GLIM criteria among patients with cancer undergoing chemotherapy. Methods: This descriptive cross-sectional study was conducted among adult cancer patients receiving chemotherapy at Prof. dr. Chairuddin P. Lubis Universitas Sumatera Utara Hospital, Medan, Indonesia, between October 2025 and January 2026. Nutritional status was assessed using the GLIM criteria. The association between cancer type and malnutrition severity was analyzed using the chi-square test. Results: A total of 107 patients were included. Lung cancer was the most common malignancy (42.1%), followed by breast (38.3%), ovarian (15.9%), and prostate cancer (3.7%). Overall, 46.7% of patients were malnourished, including 22.4% with moderate and 24.3% with severe malnutrition. The highest prevalence of malnutrition was observed in lung cancer patients (73.3%). A significant association was found between cancer type and malnutrition severity (p<0.001). Conclusion: Malnutrition is common among patients with cancer undergoing chemotherapy, and its severity varies according to cancer types.